The Practice of Introducing Restrictions on the Right to Freedom of Peaceful Assembly within Administrative Proceedings and the Place of the Judicial Branch of Power in Determining the Admissibility of Such Restrictions - M. A. Sambor (Bulletin of Kharkiv National University of Internal Affairs)
The author has researched the practice of the executive branch of power of Ukraine in establishing a collective (general) ban and restriction of the right to freedom of peaceful assembly under quarantine, as well as the place and role of the judicial branch of power represented by the Supreme Court and the Constitutional Court of Ukraine in determining the constitutionality of such restrictions and prohibitions.